Computing Equilibria when Asset Markets are Incomplete - Brown, Donald J.; Demarzo, Peter M.; Eaves, B. Curtis (Econometrica, 1996)
Existence of equilibrium with incomplete markets is problematic because demand functions are typically not continuous. Discontinuities occur at prices for which a marketed asset suddenly becomes redundant. The authors show that this discontinuity disappears if they allow an agent in the economy to introduce a new asset when such redundancies occur. This enables them to prove generic existence with incomplete markets using a standard path-following argument. Moreover, the authors' approach suggests a simple algorithm for computing equilibria when markets are incomplete. They demonstrate this by computing equilibrium for a numerical example. Copyright 1996 by The Econometric Society.